2016
DOI: 10.1103/physrevb.93.174512
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and superconductivity in ferromagnetic heavy-fermion system UCoGe under in-plane magnetic fields

Abstract: We study the ferromagnetic superconductor UCoGe at ambient pressure under ab-plane magnetic fields H, which are perpendicular to the ferromagnetic easy axis. It is shown that, by taking into account the DyaloshinskiiMoriya interaction arising from the zigzag chain crystal structure of UCoGe, we can qualitatively explain the experimentally observed in-plane anisotropy for critical magnetic fields of the paramagnetic transition. Because of this strong dependence on the magnetic field direction, upper critical fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
(96 reference statements)
2
27
0
Order By: Relevance
“…Theoretically, in UPd 2 Al 3 , it was discussed that a spin-singlet superconductivity with horizontal line nodes occurs via the virtual exchange of magnetic excitons [7,8]. In the ferromagnetic superconductors, it has been considered that the Ising-like ferromagnetic fluctuation can lead to a spin-triplet pairing state [9,10], and many fascinating phenomena including the odd H − T phase diagram have been studied [11][12][13][14][15][16]. However, in spite of the growing interest, the properties characteristic of the coexisting phase is less well understood systematically.…”
mentioning
confidence: 99%
“…Theoretically, in UPd 2 Al 3 , it was discussed that a spin-singlet superconductivity with horizontal line nodes occurs via the virtual exchange of magnetic excitons [7,8]. In the ferromagnetic superconductors, it has been considered that the Ising-like ferromagnetic fluctuation can lead to a spin-triplet pairing state [9,10], and many fascinating phenomena including the odd H − T phase diagram have been studied [11][12][13][14][15][16]. However, in spite of the growing interest, the properties characteristic of the coexisting phase is less well understood systematically.…”
mentioning
confidence: 99%
“…Mineev discussed the triplet pairing triggered by the exchange of magnetic fluctuations with a phenomenological fluctuation spectrum [23][24][25]. Tada and Fujimoto showed that the experimentally observed anomalous H c2 behaviors against T and the angle in the bc plane are well reproduced by the theoretical model with appropriately taking into account the critical FM fluctuations observed in experiments [12,26,27]. Hattori and Tsunetsugu discussed the RSC in URhGe by strong attractive interactions generated by soft magnons in the Ising systems with transverse fields [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we have shown the relationship between the Ising-type FM fluctuations and the superconductivity in UCoGe based on the 59 Co NMR measurements. From a theoretical perspective, a theoretical models of spin-triplet superconductivity observed in U-based ferromagnets were discussed by Mineev [23][24][25], and Tada and Fujimoto [12,26,27], Hattori and Tsunetsugu [28], independently. Mineev discussed the triplet pairing triggered by the exchange of magnetic fluctuations with a phenomenological fluctuation spectrum [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…2 onto the lowest two spin-dependent bands around the Fermi level 59,60 in the momentum space, and∆ 0 ( k) = ∆ 0∆ ( k) ⊗ iτ y represents the pairing potential with a pairing amplitude of ∆ 0 . In the tensor products, the first sector represents the spin channels σ =↑, ↓ shown in the caption of Table I while of 3 B 3u is energetically unfavorable rather than that of 3 B 2u , to avoid the short-range repulsion caused by the antiferromagnetic superexchange coupling along thex axis [60][61][62][63] , which can also been seen clearly in Fig. S3 in SI.…”
mentioning
confidence: 99%